Production and securitization of foreign infrastructure by "Team Korea" - Dasom Hong (Financial Internet Quarterly, 2020)
The financialization of infrastructure has emerged as a resolution for alleviating government budget pressures derived from chronic underinvestment in infrastructure and post-global financial crisis recession. Two interrelated phenomena are considered central features of the financialization of infrastructure: the transformation of infrastructure into an alternative asset class and the growth of public-private partnerships (PPPs) in infrastructure development. In particular, the expansion of global PPPs has attracted the attention of various entities, including state-owned enterprises (SOEs). Recently, SOEs have participated in foreign infrastructure PPPs as private sector entities. Unlike conventional private sector involvement in infrastructure PPPs, SOEs aim to achieve public objectives and mobilize both public and private resources to enhance competitiveness within the global PPP market. In this paper, the specificities of SOEs participating in foreign infrastructure PPPs and their implications for the financialization of infrastructure are analyzed using a South Korean SOE: Korean Overseas Infrastructure and Urban Development Corporation (KIND). This reveals why and how SOEs engage in foreign infrastructure PPPs via the drivers and business strategies of KIND. Moreover, it examines infrastructure PPPs managed by KIND to reveal how the business strategies of KIND work in practice. Consequently, this paper suggests that SOEs engaging in foreign infrastructure PPPs attempt to achieve policy objectives through the production and financialization of foreign infrastructure. In the process, SOEs actively take advantage of entities and resources from both the public and private sectors.
Keywords: R00; 330; Financial geography; financialization of infrastructure; state-owned enterprise